2020
DOI: 10.21203/rs.3.rs-31593/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medial Abrasion Syndrome:  A Neglected Cause of Persistent Pain After Knee Arthroplasty

Abstract: Background: Persistent postoperative pain (PPOP) has detracted from some otherwise successful knee arthroplasties. This study investigated medial abrasion syndrome (MAS) as a cause of PPOP after knee arthroplasty and presented the technique and outcome of arthroscopic medial release (AMR) procedure to treat such patients. Methods: In a one-year period, the author performed unicompartmental or total knee arthroplasty (the UKA or TKA group) that also eliminated MAS on 196 knees of 150 patients at advanced stages… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The plica is a fold in the synovium that represents an embryological remnant of the development of the synovial cavity in the knee. 15) Although the reported prevalence of medial plica ranges widely from 22% to 95%, 34 35) the pathological plica, characterized by inflammation, thickening, and/or reduced elasticity, can produce clinically relevant pain and crepitus. Friction between the medial plica and the facing medial femoral condyle, occurring during activities of daily living, can increase the severity of pathological changes in the medial plica and give rise to clinical symptoms, such as synovitis and pain.…”
Section: Causes Of Pathological Noisementioning
confidence: 99%
See 2 more Smart Citations
“…The plica is a fold in the synovium that represents an embryological remnant of the development of the synovial cavity in the knee. 15) Although the reported prevalence of medial plica ranges widely from 22% to 95%, 34 35) the pathological plica, characterized by inflammation, thickening, and/or reduced elasticity, can produce clinically relevant pain and crepitus. Friction between the medial plica and the facing medial femoral condyle, occurring during activities of daily living, can increase the severity of pathological changes in the medial plica and give rise to clinical symptoms, such as synovitis and pain.…”
Section: Causes Of Pathological Noisementioning
confidence: 99%
“…Friction between the medial plica and the facing medial femoral condyle, occurring during activities of daily living, can increase the severity of pathological changes in the medial plica and give rise to clinical symptoms, such as synovitis and pain. 35) Therefore, crepitus in the medial plica area requires attention if it produces a painful click. 15 34 35) …”
Section: Causes Of Pathological Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Although the prevalence of medial plica ranges widely, from 18% to 95% [22]- [24], it is generally agreed that this structure can produce knee pain and can be successfully treated by arthroscopic resection in the event that it becomes in amed, thickened, and/or less elastic [22], [25], [26]. Abrasion phenomenon between the medial plica and the opposite medial femoral condyle has been described in patients with knee OA [6], [27], [28]. The repeated injuries elicited by this abrasion phenomenon was found to trigger IL-1ß production, thus enhance the expression of MMP-3.…”
Section: Discussionmentioning
confidence: 99%
“…Sakakibara [4] reported a rate of 55% and cadaveric study showed an incidence of 34%. The prevalence was even found to be 95% in patients suffering from chronic knee pain in a cohort of more than 40-years-old individuals (Figure 1) [5].…”
Section: Introductionmentioning
confidence: 98%